Electronic properties of germanane field-effect transistors. (1st February 2017) - Madhushankar, B N; Kaverzin, A; Giousis, T; Potsi, G; Gournis, D; Rudolf, P; Blake, G R; van der Wal, C H; van Wees, B J
Abstract: A new two dimensional (2D) material—germanane—has been synthesised recently with promising electrical and optical properties. In this paper we report the first realisation of germanane field-effect transistors fabricated from multilayer single crystal flakes. Our germanane devices show transport in both electron and hole doped regimes with on/off current ratio of up to 10 5 (10 4 ) and carrier mobilities of 150 cm 2 (V · s) −1 (70 cm 2 (V · s) −1 ) at 77   K (room temperature). A significant enhancement of the device conductivity under illumination with 650   nm red laser is observed. Our results reveal ambipolar transport properties of germanane with great potential for (opto)electronics applications.